Defected and loyal? A case study of counter-defection mechanisms inside Chechen paramilitaries. Issue 4 (4th July 2018) - Souleimanov, Emil Aslan; Aliyev, Huseyn; Ratelle, Jean-François
ABSTRACT: Can former insurgents in the service of counterinsurgent paramilitaries be considered a perfectly loyal force? What mechanisms may help to deter subsequent defections of individuals who have already "betrayed" once? Drawing on a unique set of primary data, this article examines the effective counter-defection practices of Chechnya's pro-Moscow paramilitaries toward prospective defectors from among ex-insurgents. It explores three interwoven mechanisms employed with various intensities to avert "double defections" at the peak of the locally fought counterinsurgency in Chechnya from 2000 to 2005. These mechanisms are: a) extrajudicial executions of recidivists and their relatives, b) initiation violence targeting insurgents' relatives, and c) disclosure of the identities of defected insurgents who were responsible for killing insurgents in combat to the families of slain insurgents.